Analysis of speed disturbances in empirical single vehicle probe data before traffic breakdown. Issue 9 (20th September 2017) - Molzahn, Sven‐Eric; Kerner, Boris S.; Rehborn, Hubert; Klenov, Sergey L.; Koller, Micha
Abstract : In single vehicle probe data measured on German freeways the authors have revealed free flow→synchronised flow→free flow transitions that occur before traffic breakdown at a bottleneck occurs. Thus resulting in the formation of a congested pattern. The empirical findings of these phase transitions confirm a recent microscopic stochastic theory of traffic breakdown developed by Kerner. Only because of the recently introduced possibility of gathering larger amounts of anonymised vehicle data – including a sequence of positions of each car – the authors are able to show the phenomenon of these phase transitions in measured floating car data. This contribution reveals empirical findings in microscopic data which support and prove some of the recent theoretical findings of the nature of traffic breakdown.